Ground-source heat pumps : fundamentals, experiments and applications - Sarbu, Ioan; Sebarchievici, Calin; ScienceDirect eBooks (London : Academic Press, an imprint of Elsevier, 2016)
Ground-Source Heat Pumps presents the theory and some of the most recent advances of GSHPs and their implementation in the heating/cooling system of buildings. The authors explore the thermodynamic cycle with calculation, operation regimes and economic indicators and GHG emissions of a vapor compression heat pump. They go on to examine substitution strategies of non-ecological refrigerants and types of compressors and heat pumps, before delving into the different GSHP systems, as well as their compared economic, energy and environmental performances using classical and optimized adjustment for various operating modes. Surface water heat pumps and ground water heat pumps are covered, and special focus is given to both vertical and horizontal ground-coupled heat pump systems, for which modelling and simulation is discussed, and experimental systems are described. Due to its advanced approach to the subject, this book will be especially valuable for researchers, graduate students and academics, and as reference for engineers and specialists in the varied domains of building services.
5.4.5.2 The GCHPCalc Program Based on the Cylindrical Source Model5.4.5.3 Numerical Simulation Programs; 5.4.6 Simulation of Ground Thermo-Physical Capacity; 5.4.6.1 Ground Thermal Response Test; 5.4.6.2 Equivalent-Time for Interrupted Tests on BHE; 5.4.6.3 Use of EED Simulation Program; 5.4.7 One-Dimensional Transient BHE Model; 5.4.7.1 Model Description; 5.4.7.2 Solution Methodology; 5.4.8 Modelling the Interactions Between Ground Temperature Variations and Performance of GCHPs; 5.4.8.1 Model Description; 5.4.8.2 Model Validation
Includes bibliographical references and index.
Online resource; title from PDF title page (EBSCO, viewed October 8, 2015).
Elsevier
Keywords: Ground source heat pump systems; TECHNOLOGY & ENGINEERING / Construction / Heating, Ventilation & Air Conditioning; Ground source heat pump systems; Electronic books